Advanced Nanoparticles in Combating Antibiotic Resistance: Current Innovations and Future Directions - Dana Mohammed AlQurashi; Tayf Fahad AlQurashi; Raneia Idrees Alam; Sumera Shaikh; Mariam Abdulaziz M. Tarkistani (Journal of Nanotheranostics, 2025)
Antibiotic resistance poses a significant global health challenge, undermining the effectiveness of conventional treatments and increasing mortality rates worldwide. Factors such as the overuse and misuse of antibiotics in healthcare and agriculture, along with poor infection control practices, have accelerated the emergence of resistant bacterial strains. The stagnation in the development of new antibiotics, compounded by economic and biological challenges, has necessitated alternative approaches to combat resistant infections. Nanotechnology provides a promising solution using nanoparticles (NPs), which combat bacteria through mechanisms like membrane disruption and reactive oxygen species (ROS) generation. Metal-based nanoparticles such as silver and zinc oxide possess intrinsic antimicrobial properties, while polymer- and carbon-based nanoparticles enhance drug delivery and biofilm penetration. Unlike conventional antibiotics, nanoparticles operate through multi-mechanistic pathways, reducing the likelihood of resistance development and improving treatment efficacy. This review aims to provide an updated, in-depth look at recent advances in nanoparticle research targeting antibiotic resistance, discussing different types of nanoparticles, mechanisms of action, and current challenges and opportunities. By exploring the evolving role of nanotechnology in addressing this crisis, this review intends to highlight the potential for nanoparticles to transform the treatment landscape for resistant bacterial infections and inspire further research into these innovative solutions.